No effect of caloric restriction or exercise on radiation repair capacity - Habermann, Nina; Abbenhardt-Martin, Clare; Ulrich, Cornelia (Medicine and science in sports and exercise, 2015)
Introduction Maintenance of normal weight and higher levels of physical activity are associated with a reduced risk of several types of cancer. As genomic instability is regarded as a hallmark of cancer development, one proposed mechanism is improvement of DNA repair function. We investigated links between dietary weight loss, exercise, and strand break rejoining in an ancillary study to a randomized-controlled trial. Methods Overweight/obese postmenopausal women (n=439) were randomized to: a) reduced-calorie weight-loss diet (“diet” n=118); b) moderate-to-vigorous intensity aerobic exercise (“exercise” n=117); c) a combination (“diet+exercise” n=117); or d) control (n=87). The reduced-calorie diet had a 10% weight-loss goal. The exercise intervention consisted of 45 minutes of moderate-to-vigorous aerobic activity 5 days/week for 12 months. DNA repair capacity was measured in a subset of 226 women at baseline and 12 months, from cryopreserved peripheral mononuclear cells using the Comet assay. Anthropometric and body composition measures were performed at baseline and 12 months. Results DNA repair capacity did not change significantly with any of the 12 month interventions compared to control; there were also no significant changes when stratified by changes in body composition or aerobic fitness (VO2max). At baseline, DNA repair capacity was positively associated with weight, BMI, and fat mass (r=0.20, p=0.003; r=0.19, p=0.004; r=0.13, p=0.04, respectively) and inversely with lean body mass (r=-0.14, p=0.04). Conclusion In conclusion, DNA repair capacity did not change with dietary weight loss or exercise interventions in postmenopausal women within a period of 12 months. Other assays that capture different facets of DNA repair function may be needed.